(Un)documenting single-panel methodologies and epistemologies in the non-fictional cartoons of Eric J. García and Alberto Ledesma. Issue 2 (3rd May 2020) - Urcaregui, Maite
ABSTRACT: This article analyzes how two Latinx cartoonists, Eric J. García and Alberto Ledesma, use the single-panel form to critique and reshape national discourses of immigration, citizenship, and the US-Mexico border. By distilling non-fictional referents and triangulating multiple perspectives, the single-panel cartoon is uniquely positioned to portray the complex epistemological stakes of immigration and documentation. García's pointed editorial cartoons offer a structural critique of the policies and laws that create the category of "undocumented" to exploit and criminalize immigrants. Ledesma's cartoons draw from personal narrative to highlight the more intimate effects of this status and how it gives undocumented individuals a critical awareness of the systems and institutions they navigate. Through the single-panel cartoon, these artists bring the material realities of the U.S.-Mexico border and the U.S.'s criminal and criminalizing immigration policies into view for their reader and, in doing so, help to reshape their perspective on these issues.